A Model of Servitization of SMES Operations: A Case Analysis - Maciej SZCZEPANCZYK; Pawel PIETRAS (Communications of International Proceedings, 2021)
This article presents the methodology of implementing the servitization process within the enterprise. This methodology was elaborated by authors working with the international project team and then implemented in nine polish companies in MSE sector located in the center of Poland. Presented approach divide the implementation project into two separate phases. The article presents the short description of both phases and the main data and conclusions after the implementation.
Keywords: Services; Service Innovation; Servitization; Innovative; Company Development Management.